Cross-regulation between Aurora B and Citron kinase controls midbody architecture in cytokinesis. Issue 3 (March 2016) - McKenzie, Callum; Bassi, Zuni I.; Debski, Janusz; Gottardo, Marco; Callaini, Giuliano; Dadlez, Michal; D'Avino, Pier Paolo
Abstract : Cytokinesis culminates in the final separation, or abscission, of the two daughter cells at the end of cell division. Abscission relies on an organelle, the midbody, which forms at the intercellular bridge and is composed of various proteins arranged in a precise stereotypic pattern. The molecular mechanisms controlling midbody organization and function, however, are obscure. Here we show that proper midbody architecture requires cross-regulation between two cell division kinases, Citron kinase (CIT-K) and Aurora B, the kinase component of the chromosomal passenger complex (CPC). CIT-K interacts directly with three CPC components and is required for proper midbody architecture and the orderly arrangement of midbody proteins, including the CPC. In addition, we show that CIT-K promotes Aurora B activity through phosphorylation of the INCENP CPC subunit at the TSS motif. In turn, Aurora B controls CIT-K localization and association with its central spindle partners through phosphorylation of CIT-K's coiled coil domain. Our results identify, for the first time, a cross-regulatory mechanism between two kinases during cytokinesis, which is crucial for establishing the stereotyped organization of midbody proteins.